In Situ Quantification of Strain‐Induced Piezoelectric Potential of Dynamically Bending ZnO Microwires. Issue 3 (22nd January 2023) - Zhang, Hao; Gao, Haibo; Geng, Junyuan; Meng, Xianghe; Xie, Hui
Abstract: The piezoelectric properties of semiconductor micro/nanowires (M/NWs) are crucial for optimizing semiconductors' electronic structure and carrier dynamics. However, the dynamic characterization of the piezoelectric properties of M/NWs remains challenging. Here, a Kelvin probe force microscopy technique based on a dual‐probe atomic force microscope is developed to achieve in situ piezoelectric potential measurements of dynamic bending MWs. This technique can not only characterize the surface potential on different crystal faces of ZnO MWs in a natural state through controllable axial rotation, but also investigate the piezoelectric potential of the dynamically bending flake‐like ZnO MW at different points and under different strain loads. The results show that the surface potentials of different faces/positions of the ZnO MWs are varied significantly, and determine that the quasi‐static conditions piezo‐strain factor of the flake‐like ZnO MW is 0.28 V/%, while the factor was 0.14 V/% under low‐frequency (⩽5 Hz) sinusoidal strain loading. This work provides a significant methodology to further study piezoelectric materials, and it aims to facilitate their applications in piezoelectric devices and systems. Abstract : This paper proposes a Kelvin probe force microscopy technique based on a dual‐probe atomic force microscope. It can not only characterizes the surface potentials of different crystal faces of microwires in a natural state through controllable axial rotation, but also directly in situ detect the piezoelectric potentials of dynamically bending microwires, which promotes the development of piezoelectric device technology.